The apoptotic potential of ergolide to induce apoptosis in molt4 cell lines - Amir Yami; Maryam Hamzeloo-Moghadam; Afshin Karami; Mohyedin Barzegar; Vahid Amiri; Ahmad Gharehbaghian (Institue of Medicinal Plants, ACECR, 2020)
Background: Cancer is a multi-faceted diseases caused cell proliferation in an out of control manner due to accumulation of defects and mutation in their DNA and with an impendence to invade or spread to parts of the body. During last decades new compounds with natural roots have emerged as a new paradigm for effective anti-cancer treatment. Objective: The aim of this study is to evaluate the potential of ergolide a sesquiterpene lactone with multi-functional history to induce apoptosis. Methods: Ergolide from Inula-Oculus-Christi a sesquiterpene lactone from Asteraceae plant was extracted by Traditional Medicine Research Center of Shahid Beheshti University of Medical Sciences. The cytotoxic effects of Ergolide on the acute lymphoblastic leukemia (MOLT4) and PBMC (normal cell line) were investigated at different doses for 48 hours. In this study, MTT assay and acridine orange staining were used. Also, annexin V-PI assays was utilized for further evaluation. In addition the gene expression level of BAX and BCL2 were analyzed by q-RealTime-PCR (quantitive RT-PCR). Results: The results of MTT assay demonstrated the induction of apoptosis and reduction in proliferation of MOLT4 cells treated by ergolide. (P < 0.001). Interestingly Ergolide could be less toxic in normal cells (PBMCs). AO staining and Flow cytometry analysis confirmed a significantly high percentage of autophagic and apoptotic cells compared with control groups respectively (P < 0.05). Conclusion: According to the results, ergolide demonstrated cytotoxic effects on MOLT-4, but further studies are needed to confirm its effectiveness as a complementary agent in the treatment of acute lymphoblastic leukemia.